Learning the Nuclear : Educational Tourism in (Post)Industrial Sites. - Mazeikienė, Natalija. (New Approaches in Educational and Social Sciences / Neue Denkansaetze in Den Bildungs- und Sozialwissenschaften Series, 2021)
The book illuminates the educational potential of nuclear tourism that becomes a site of outdoor and place-based education, promotes STEM, energy literacy, critical thinking, and environmental skills.